1986
DOI: 10.1007/bf01611728
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric parameters of Müller (glial) cells dependent on their topographic localization in the nonmyelinated part of the rabbit retina. A consideration of functional aspects of radial glia

Abstract: Morphometric parameters of Müller cells were evaluated by light microscopy both in whole retinae and in enzymatically isolated cells from adult pigmented rabbits. In spite of the marked decrease in cell densities from visual streak to far periphery, a constant glia-neuron ratio of about 1:15 was found in all regions. The volume of individual Müller cells was found to increase strongly when the cells become shorter, i.e. when the retinal centre was compared to the retinal periphery. The contribution of Müller c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 29 publications
4
25
0
1
Order By: Relevance
“…Compared to data on other mammals (Reichenbach and Wohlrab, 1986;Dreher et al, 1988Dreher et al, , 1992Reichenbach et al, 1991: 4,000-15,000 Muller cells/mm2), the estimated density of tree shrew Miiller cells (12,000-24,000/mm2) is rather high. However, published data on densities of ganglion cells (DeBruyn, 1983;Miiller, 1987) and photoreceptor cells (Miiller and Peichl, 1989;Miiller et al, 1989;Petry et al, 1993) are quite similar or even identical to what we found in our study.…”
Section: Neuron-to-(mul1er)glia Ratio Of the Tree Shrew Retinamentioning
confidence: 75%
See 1 more Smart Citation
“…Compared to data on other mammals (Reichenbach and Wohlrab, 1986;Dreher et al, 1988Dreher et al, , 1992Reichenbach et al, 1991: 4,000-15,000 Muller cells/mm2), the estimated density of tree shrew Miiller cells (12,000-24,000/mm2) is rather high. However, published data on densities of ganglion cells (DeBruyn, 1983;Miiller, 1987) and photoreceptor cells (Miiller and Peichl, 1989;Miiller et al, 1989;Petry et al, 1993) are quite similar or even identical to what we found in our study.…”
Section: Neuron-to-(mul1er)glia Ratio Of the Tree Shrew Retinamentioning
confidence: 75%
“…This is in contrast to Muller cells of other mammalian species, which express an inverse proportionality between cell length and process diameter (our own unpublished results in 18 mammalian species; Dreher et al, 1992). A rabbit Muller cell of 60 pm length would be expected to have a vitread trunk with a diameter of 7 km (Reichenbach and Wohlrab, 1986;Reichenbach et al, 1991;Dreher et al, 1992), whereas, in tree shrew cells, diameters of less than 1 pm were estimated.…”
Section: Shape Of Tree Shrew Miiller Cellsmentioning
confidence: 91%
“…Mü ller glial cell bodies are located in the middle of the inner nuclear layer, extending processes radially to the outer and inner limiting membranes. They have different morphologies and functions, depending on the region of the retina, center or periphery (Reichenbach and Wohlrab, 1986;Newman, 1987;Eberhardt and Reichenbach, 1987), as well as in vascular and avascular retinas (Dreher et al, 1992 Although small GTPases from the Rho family are key regulators of actin polymerization, they also affect other cytoskeleton components in certain cell types. In cultured Mü ller cells we showed colocalization of RhoB with vimentin, suggestive of a potential role for RhoB in the regulation of vimentin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial buffer currents flow through Mü ller cells via their conducting cables, i.e., the inner stalk processes of Mü ller cells extending between the soma (i.e., close to the sources of K ϩ ) and the endfeet (where K ϩ is to be released). In all vertebrate retinae studied, Mü ller cells from (thick) central retina have thin and long stalk processes, whereas cells from (thin) peripheral retina possess shorter and thicker stalks (Reichenbach and Wohlrab, 1986;Reichenbach et al, 1995). For the rabbit retina, such geometric data have been used for mathematical modeling of the cable properties of peripheral and central Mü ller cell stalk processes (Eberhardt and Reichenbach, 1987).…”
Section: Introductionmentioning
confidence: 98%